The electronic commerce in the travel agencie's activities in Bulgaria and terms of reference for its elaboration - Velina Kazandzhieva (UTMS Journal of Economics, 2010)
The data used in the paper and the sources of information studied, show regaining of the positions and the role of travel agencies in the distribution system of tourism. The main trends and special features of the European on-line tourist market have been analyzed, as well as the state of the electronic commerce in travel agencies in Bulgaria. Alternatives and values-generating strategies for the intermediary business through efficient use of the advantages of -commerce have been pointed out.
Keywords: 330; Internet; travel agencies; electronic commerce; value